LRH‐1/NR5A2 targets mitochondrial dynamics to reprogram type 1 diabetes macrophages and dendritic cells into an immune tolerance phenotype - Nadia Cobo‐Vuilleumier; Silvia Rodríguez‐Fernandez; Livia López‐Noriega; Petra I. Lorenzo; Jaime M. Franco; Christian C. Lachaud; Eugenia Martin Vazquez; Raquel Araujo Legido; Akaitz Dorronsoro; Raul López‐Férnandez‐Sobrino; Beatriz Fernández‐Santos; Carmen Espejo Serrano; et al. (Clinical and Translational Medicine)
Abstract Background The complex aetiology of type 1 diabetes (T1D), characterised by a detrimental cross‐talk between the immune system and insulin‐producing beta cells, has hindered the development of effective disease‐modifying therapies. The discovery that the pharmacological activation of LRH‐1/NR5A2 can reverse hyperglycaemia in mouse models of T1D by attenuating the autoimmune attack coupled to beta cell survival/regeneration prompted us to investigate whether immune tolerisation could be translated to individuals with T1D by LRH‐1/NR5A2 activation and improve islet survival. Methods Peripheral blood mononuclear cells (PBMCs) were isolated from individuals with and without T1D and derived into various immune cells, including macrophages and dendritic cells. Cell subpopulations were then treated or not with BL001, a pharmacological agonist of LRH‐1/NR5A2, and processed for: (1) Cell surface marker profiling, (2) cytokine secretome profiling, (3) autologous T‐cell proliferation, (4) RNAseq and (5) proteomic analysis. BL001‐target gene expression levels were confirmed by quantitative PCR. Mitochondrial function was evaluated through the measurement of oxygen consumption rate using a Seahorse XF analyser. Co‐cultures of PBMCs and iPSCs‐derived islet organoids were performed to assess the impact of BL001 on beta cell viability. Results LRH‐1/NR5A2 activation induced a genetic and immunometabolic reprogramming of T1D immune cells, marked by reduced pro‐inflammatory markers and cytokine secretion, along with enhanced mitohormesis in pro‐inflammatory M1 macrophages and mitochondrial turnover in mature dendritic cells. These changes induced a shift from a pro‐inflammatory to an anti‐inflammatory/tolerogenic state, resulting in the inhibition of CD4+ and CD8+ T‐cell proliferation. BL001 treatment also increased CD4+/CD25+/FoxP3+ regulatory T‐cells and Th2 cells within PBMCs while decreasing CD8+ T‐cell proliferation. Additionally, BL001 alleviated PBMC‐induced apoptosis and maintained insulin expression in human iPSC‐derived islet organoids. Conclusion These findings demonstrate the potential of LRH‐1/NR5A2 activation to modulate immune responses and support beta cell viability in T1D, suggesting a new therapeutic approach. Key Points LRH‐1/NR5A2 activation in inflammatory cells of individuals with type 1 diabetes (T1D) reduces pro‐inflammatory cell surface markers and cytokine release. LRH‐1/NR5A2 promotes a mitohormesis‐induced immuno‐resistant phenotype to pro‐inflammatory macrophages. Mature dendritic cells acquire a tolerogenic phenotype via LRH‐1/NR5A2‐stimulated mitochondria turnover. LRH‐1/NR5A2 agonistic activation expands a CD4+/CD25+/FoxP3+ T‐cell subpopulation. Pharmacological activation of LRH‐1/NR5A2 improves the survival iPSC‐islets‐like organoids co‐cultured with PBMCs from individuals with T1D.